Mitochondrial DNA as a Biomarker for Acute Central Serous Chorioretinopathy: A Case-Control Study - Hashida, Noriyasu; Asao, Kazunobu; Hara, Chikako; Quantock, Andrew J.; Saita, Ryotaro; Kurakami, Hiroyuki; Maruyama, Kazuichi; Nishida, Kohji (Frontiers in Medicine, 2022)
Background: The literature suggests that stress may play a pivotal role in the precipitation of acute central serous chorioretinopathy (CSC) because chorioretinal integrity can be affected by the psychosocial state of the patient, indicating the need for a biomarker. Not only physical stress but also psychological stress causes many types of physical disorders. However, little is known about the pathophysiology of stress-induced disease. The objective of this study was to investigate whether serum factors might be involved in the development of stress-induced ocular diseases. Methods: This observational case series included 33 eyes of 33 consecutive patients with treatment-naïve acute CSC. Fifty eyes of 50 age-matched healthy volunteers were included in this study as non-CSC controls. Serum samples were collected from all participants, and the levels of mitochondrial DNA (mtDNA) were measured by quantitative real-time (RT)-PCR. Serum levels of high-mobility group box (HMGB) 1 and 8-hydroxy-2’-deoxyguanosine (8-OHdG), biological markers of acute/chronic inflammation and oxidative stress, were also measured. The relationships between serum mtDNA, 8-OHdG, and HMGB1 concentrations were investigated by multivariate regression analysis, alongside an assessment of clinical data. Results: In the treatment-naïve acute CSC group, the serum mtDNA levels (36.5 ± 32.4 ng/mL) were significantly higher than the levels in the control group (7.4 ± 5.9 ng/mL; p < 0.001). Serum levels of 8-OHdG and HMGB1 in treatment-naïve acute CSC patients measured 0.12 ± 0.08 ng/mL and 18.1 ± 35.0 ng/mL, respectively, indicating that HMGB1 levels were elevated in CSC compared with the control group. Multivariable regression analysis demonstrated that increased serum mtDNA levels were significantly associated with the height of serous retinal detachment. Conclusions: We showed serum mtDNA and HMGB1 level elevation and its relation to the clinical activities of CSC, indicating that serum mtDNA and HMGB1 could serve as biomarkers for the acute phase of the disease. The use of these biomarkers makes it possible to predict disease onset and determine disease severity.